2016
DOI: 10.19082/1740
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Occupational Noise Exposure on Blood and Biochemical Parameters: A Case Study of an Insulator Manufacturer in Iran

Abstract: IntroductionOccupational noise is among the most critical occupational hazards, which, in addition to hearing loss, can cause other adverse consequences on an individual’s physical and mental health. Long-term exposure to noise can affect blood and biochemical parameters and subsequently lead to increased risk of cardiovascular disease. This study investigated the effect of occupational exposure to noise on blood and biochemical parameters of workers in an insulator manufacturing plant.MethodsThis case-control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 20 publications
(22 reference statements)
0
15
2
2
Order By: Relevance
“…The authors noted that in the Czech Republic, 75% of workers exposed to noise in textile production are observed to be female, followed by 5% in food production. Mohammadi et al [7] observed a significant effect of occupational noise on the blood biochemical parameters of workers in an Iranian insulator manufacturing plant. A relationship between exposure to noise and significantly increased systolic blood pressure of 62 male workers in a sack manufacturing company was found in Nigeria [8].…”
Section: Introductionmentioning
confidence: 99%
“…The authors noted that in the Czech Republic, 75% of workers exposed to noise in textile production are observed to be female, followed by 5% in food production. Mohammadi et al [7] observed a significant effect of occupational noise on the blood biochemical parameters of workers in an Iranian insulator manufacturing plant. A relationship between exposure to noise and significantly increased systolic blood pressure of 62 male workers in a sack manufacturing company was found in Nigeria [8].…”
Section: Introductionmentioning
confidence: 99%
“…There are a lot of job environments that are highly exposed to silica, for instance, ironworking, mining and painting, pottery and ceramics factories, foundries, and insulator manufacturers (Greenberg et al, 2007; Mohammadi et al, 2017b; Steenland and Ward, 2014). Isolator is a device with a very high electrical resistance that is used as an electrical insulation between two conductors with different voltages and between a conductor and earth (Mohammadi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The concentration exposure of silica is a determinative factor in the development of silicosis. [ 5 ] The diagnosis of silicosis is possible when it has progressed and person has been involved. Therefore, it is important to propose appropriate biomarkers to identify the high-risk exposures.…”
Section: Discussionmentioning
confidence: 99%
“…During most of its manufacturing processes such as milling, mixing, pressing, assembling, cutting, grinding, and extruding equipment, there is the possibility of emitting silica particles. [ 5 ]…”
Section: Introductionmentioning
confidence: 99%